RESULTS OF DETECTION OF COLONIC DYSBACTERIOSIS IN THYMECTOMIZED LABORATORY ANIMALS - Umida M. Nuralieva (Central Asian Journal of Medicine, 2023)
Experimental studies have been carried out to investigate the state of microflora of the large intestine 1, 3 and 6 months after thymectomy. The obtained data indicate the appearance of intestinal dysbacteriosis as a result of thymectomy. A decrease in indigeneous and facultative microflora in the first months after thymectomy leads to an increase in transient microflora. In 3 and 6 months after thymectomy there is a quantitative decrease of transient microflora against the background of quantitative recovery of facultative microflora. At decrease (or absence) of regulatory function of the immune system, colonisation activity and colonisation resistance of the microorganism itself come first, this provides survival of these microorganisms, as well as rapid quantitative recovery.